Does Osteopathic Manipulative Treatment Induce Autonomic Changes in Healthy Participants? A Thermal Imaging Study - Cerritelli, Francesco; Cardone, Daniela; Pirino, Alessio; Merla, Arcangelo; Scoppa, Fabio (Frontiers in Neuroscience, 2020)
Osteopathic manipulative treatment (OMT) has been demonstrated to be an effective therapy in several clinical conditions and age groups. Despite the clinical effectiveness, lack of robust data in terms of neurobiological, specifically autonomic, mechanisms of action is observed. Preliminary studies showed a parasympathetic effect leading to a trophotropic effect of OMT. However, these data are limited to heart rate variability (HRV) analysis. In order to study further the role of OMT on the autonomic nervous system, a cross-over randomized controlled trial RCT has been designed to test the effect of osteopathic treatment compared to sham therapy on a range of autonomic parameters. Thermal images, HRV and skin conductance data were collected on a sample of healthy adults. The study design consisted of two sessions (OMT and SHAM), 1 treatment per week, lasting 35 minutes each, composed of 5 minutes of baseline, 25 minutes of treatment, and 5 minutes of post-touch. During the baseline and the post-treatment, participants received no touch. 37 participants (aged 27±5 years old, male ratio 40%) completed the study. Multivariate analysis showed a significant parasympathetic effect of group as well as of epoch on thermographic data of the nose (estimate 0.38; 95% CI 0.12 – 0.63; p<0.01), left (0.17; 0.06 – 0.27; <0.001) and right (0.16; 0.07 – 0.24; <0.001) perioral as well as on the forehead (0.07; 0.01 – 0.12; <0.01) regions but not for the chin (0.08; -0.02 – 0.18; 0.13). Consistent with a parasympathetic effect, analyses demonstrated a difference between OMT and sham groups on the nuHF (p < 0.001) and DFA-a1 (p<0.01) as well as on skin conductance (<0.01). The present research supports the hypothesis that a single session of osteopathic manipulative treatment as compared to sham induces autonomic consequences in healthy non-symptomatic adults. Clinicaltrial.gov identifier: NCT03888456 https://clinicaltrials.gov/ct2/show/NCT03888456